Communication management aimed at building participation: the experience of the Participatory Institutional Plan of the National University of Entre Ríos - Andretich, Gabriela V.; Deluca, Elisa; Sosa Passarino, Emilia P. (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
Like the entire university planning process, the construction of the 2018-2022 Participatory Institutional Plan of the National University of Entre Ríos involves various interactions and shapes multiple communicative practices, as well as the constant exchange of directions. This article focuses on the communication strategies deployed in this journey and on communication as a decisive dimension to plan from a participatory perspective that, consequently, constitutes a support tool for university management. From the analysis of this experience, a dialogue between the concepts of communication and participation is proposed, whose dialectic allows deepening the specific framework of situational strategic planning and enabling the appropriation of the plan by the academic community. In this framework, the logics imposed by the current cultural ecosystem gestated in the age of information, knowledge, digitality and convergence, which constantly transform contemporary social-cultural ties, are problematized.